Extreme values of ET0 at Piracicaba, Brazil, for designing irrigation systems - Verônica G. M. L. de Melo; José A. Frizzone; Leonardo L. de Melo; Antonio P. de Camargo (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Irrigation system capacity is typically defined by analyzing probabilities of non-exceedance of evapotranspiration. The use of mean monthly values of ET0 may lead to underestimation of the required capacity, whereas use of maximum daily values may result in overestimation of required capacity. This study had the following objectives: (1) to analyze a 30-year series of daily ET0 data from Piracicaba, SP, Brazil, to evaluate the suitability of the Gumbel distribution for estimating the maximum values of ET0 organized in periods of up to 30 days; (2) to determine probable maximum values and to select ET0 values considering the irrigation interval and the risk of failure in terms of irrigation system capacity. Daily data from 1990 to 2019 were used to calculate ET0 using the Penman-Monteith model. The Gumbel distribution fitted to the data and was suitable for characterizing the frequency distribution of the maximum ET0. The probable ET0 for designing irrigation systems can then be estimated based on the expected lifespan, irrigation interval, and return period of ET0 maximum values. The higher the anticipated irrigation system lifespan, the higher the return period needed to attain a low risk of failure. Using the average of maximum ET0 values alone leads to underestimation of system capacity and a high risk of failure in terms of irrigation system capacity.